Patient navigators: Mapping the route toward accessibility in health care. Issue 1 (18th May 2018) - Rollins, Meaghen; Milone, Francine; Suleman, Shazeen; Vojvoda, Dorjana; Sgro, Michael; Barozzino, Tony
Abstract: Children and youth with developmental and mental health conditions require a wide range of clinical supports and social services to improve their quality of life. However, few children and youth are currently able to adequately access these clinical, community and social services, and newcomers or those living in poverty are even further disadvantaged. Patient navigator programs can bridge this gap by facilitating connections to social services, supporting family coping strategies and advocating for patient clinical services. Although there are few paediatric-focused patient navigator programs in the literature, they offer the potential to improve short and long-term health outcomes. As social and clinical services, particularly for developmental and mental health conditions, become increasingly complex and restricted, it is important that physicians and policymakers consider implementing patient navigator programs with a rigorous evaluation framework to improve accessibility and health outcomes. This can ultimately facilitate policymakers in creating more equitable resources in challenging fiscal climates.